Electromagnetic Funnel: Reflectionless Transmission and Guiding of Waves through Subwavelength Apertures - Mohammadi Estakhri, Nasim; Engheta, Nader; Kastner, Raphael (Physical review letters, 2020)
Confining and controlling electromagnetic energy typically involves a highly resonant phenomenon, especially when subwavelength confinement is desired. Here, we present a class of nonresonant, self-dual planar metastructures capable of protected energy transmission from one side to the other, through arbitrarily narrow apertures. It is shown that the transmission is in the form of matched propagating modes and is independent of the thickness and specific composition of the surface. We analytically prove that the self-dual condition is sufficient to guarantee 100% transmission that is robust to the presence of discontinuities along the propagation path. The results are confirmed numerically through study of various scenarios. The operation is broadband and subject only to the bandwidth of the constituent materials. The polarization of the internal field can also be independently controlled with respect to the incident one. Our structures are promising for applications in sensing, particle trapping, near-field imaging, and wide scan antenna arrays.